IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2018 TENTANGKEKARANTINAAN KESEHATAN DI JAWA TIMUR MENGHADAPI PANDEMI COVID 19 - Iman Pasu Purba (Jurnal Pahlawan, 2021)
World Health Organization (WHO) has declared that Corona Virus Disease 2019 (Covid 19) is a pandemic in the whole world. The spread of Covid 19 in Indonesia has been affected because Covid 19 is increasingly widespread across regions and across countries accompanied by an increase in the number of cases and / or the number of deaths. In facing this pandemic, Indonesia will refer to Law Number 6 of 2018 concerning Health Quarantine. One of the provinces most affected because it is marked by the high number of people who have contracted Covid 19 is East Java Province. As of January 2021, the number of Covid 19 patients has approached 90,000 people. Therefore, the East Java Government is obliged to enforce regulations regarding health quarantine in order to suppress the growth rate of Covid 19 in East Java. It is necessary to study the implementation of these regulations as material for information and evaluation both for the government and for the Indonesian people, especially residents of East Java. The implementation of the substance of the law on health quarantine becomes a reference to measure the extent to which the legal culture of the community and the quality of enforcement of this health quarantine rule in East Java. The East Java government implements health quarantine by implementing Large-Scale Social Restrictions (PSBB), budget refocusing and other tactical policies to protect all its citizens, such as the constitutional mandate and laws